1992
DOI: 10.1007/bf01948003
|View full text |Cite
|
Sign up to set email alerts
|

A sensorory input inhibiting heart rate in an insect,Rhodnius prolixus

Abstract: Canada L9G 3N6), andAbstract. The dorsal vessel of the blood feeding insect, Rhodnius prolixus, was found to increase or decrease its rate of contraction in response to a number of different stimuli. Handling increased contraction rates whereas tactile stimulation of the ventral abdominal cuticle inhibited contraction. Injection of very low concentrations of serotonin or of high concentrations of octopamine enhanced the inhibitory effect, apparently by acting via the nervous system. Higher concentrations of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 16 publications
1
25
0
1
Order By: Relevance
“…The dorsal vessel is capable of producing rates of flow approaching 4·l·min -1 (Amaka Enh, personal communication) and so may play a significant role in the circulation of haemolymph and hormones. Previous studies have examined the contraction of the heart and dorsal vessel of R. prolixus (Chiang et al, 1992;Sarkar et al, 2003). Interestingly, both serotonin (Chiang et al, 1992) and Rhopr/Dippu-DH 31 (this study) increase the frequency of contractions in a dose-dependent manner, with cyclic AMP possibly acting as the second messenger.…”
Section: A Te Brugge D a Schooley And I Orchardmentioning
confidence: 53%
“…The dorsal vessel is capable of producing rates of flow approaching 4·l·min -1 (Amaka Enh, personal communication) and so may play a significant role in the circulation of haemolymph and hormones. Previous studies have examined the contraction of the heart and dorsal vessel of R. prolixus (Chiang et al, 1992;Sarkar et al, 2003). Interestingly, both serotonin (Chiang et al, 1992) and Rhopr/Dippu-DH 31 (this study) increase the frequency of contractions in a dose-dependent manner, with cyclic AMP possibly acting as the second messenger.…”
Section: A Te Brugge D a Schooley And I Orchardmentioning
confidence: 53%
“…Serotonin also influences the frequency of heart contractions in multiple insect species. For example, serotonin increases the heart rate of Periplaneta americana, Rhodnius prolixus, and Manduca sexta in a concentration-dependent manner, with the confirmed bioactive concentrations ranging from 1 X10 -9 M to 1 X10 -5 M (Chiang et al, 1992;Collins and Miller, 1977;Platt and Reynolds, 1986;Prier et al, 1994). In D. melanogaster, several studies have shown that serotonin is cardioacceleratory, with the confirmed bioactive concentrations ranging between 1 X 10 -7 M and 1 X 10 -5 M (Johnson et al, 1997;Johnson et al, 2002;Majeed et al, 2013;Nichols, 2006;Zornik et al, 1999).…”
Section: Discussionmentioning
confidence: 94%
“…This behaviour is mediated by negative phototaxis , by assembling signals (Schofield & Patterson 1977, Lorenzo & Lazzari 1996, Lorenzo Figueiras & Lazzari 1998) and by thigmotaxis. The last response is mediated by mechanoreceptive inputs coming from the whole body surface, is able to induce certain physiological changes in the bugs, such as a decrease in the heart rate (Chiang et al 1992). Thus, head hairs could play a role in maintaining thigmotaxis and triggering physiological responses associated with this behaviour.…”
Section: Discussionmentioning
confidence: 99%